2004
DOI: 10.1073/pnas.0407733101
|View full text |Cite
|
Sign up to set email alerts
|

Use of coherent control methods through scattering biological tissue to achieve functional imaging

Abstract: We test whether coherent control methods based on ultrashortpulse phase shaping can be applied when the laser light propagates through biological tissue. Our results demonstrate experimentally that the spectral-phase properties of shaped laser pulses optimized to achieve selective two-photon excitation survive as the laser pulses propagate through tissue. This observation is used to obtain functional images based on selective two-photon excitation of a pH-sensitive chromophore in a sample that is placed behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…[15][16][17] However, to the best of our knowledge, this is the first demonstration of pulse-pair control in microscopy with possibilities of controlling molecular fluorescence in microscopy using rather simple pulse-pair excitation. Now, to explain time-domain quantum control using phase-locked pulse-sequence, consider Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[15][16][17] However, to the best of our knowledge, this is the first demonstration of pulse-pair control in microscopy with possibilities of controlling molecular fluorescence in microscopy using rather simple pulse-pair excitation. Now, to explain time-domain quantum control using phase-locked pulse-sequence, consider Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Several research groups have shown the applications of control schemes in various nonlinear imaging, e.g., multiphoton fluorescence microscopy [15][16][17] and coherent anti-Stokes Raman scattering microscopy. 18 All efforts are based on laser pulse shaping, where each pulse is shaped in phase ͑and/or intensity͒.…”
Section: Resultsmentioning
confidence: 99%
“…Control of two-photon excitation by shaping femtosecond laser pulses has been demonstrated [10], [11]. Sinusoidal phase shaping [12], binary phase shaping [13], antisymmetric phase shaping [14], and adaptive phase shaping [15] of ultrafast pulses have been demonstrated to selectively image fluorophores in biological samples. While phase-only shaping techniques have been studied extensively in TPF imaging, the potential of amplitude shaping has not been fully utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of photons both in space [16] and in time [17] seems to leave little room for coherent control in nonlinear microscopy and spectroscopy. As demonstrated in [18], high resolution nonlinear optical imaging through a scattering biological medium can be carried out as long as ballistic (i.e. non-scattered or weakly scattered) photons are available for the required spectral phase modulation.…”
Section: Introductionmentioning
confidence: 99%